Spectrophotometric Determination of Glutathione Based Inhibitory Effect on Hemoglobin - Hong Chen, Ya; Shou Tian, Feng; Jiang, Rui (Asian Journal of Chemistry, 2010)
A high sensitive and simple catalytic spectrophotometric method for the determination of reduced glutathione based on its inhibitory effect on the hemoglobin-cayalyzed the reaction of H2O2 and acid chrome blue K(ACBK) was developed. The concentration of glutathione is linear with the percentage inhibition (I %) of system under the optimal experimental conditions. The calibration graph is linear in range 1.82 × 10-7 to 4.55 × 10-5 mol L-1 with the detection limit of 3.49 × 10-8 mol L-1. The relative standard deviation was 3.97 % for 11 determinations of 1.82 × 10-5 mol L-1. This method can be used for the determination of glutathione in pharmaceuticals and vegetables with satisfactory results.